Electrodeposited zinc grid as low‐cost solar cell front contact. (18th April 2016) - Tsin, Fabien; Rousset, Jean; Le Bris, Arthur; Lincot, Daniel
Abstract: This paper presents an innovative low‐cost electrodeposition process to grow metallic zinc grids as a front contact for Cu(In, Ga)(Se, S)2 (CIGS) and silicon heterojunction solar cells as an alternative to complex and expensive monolithic integration and silver screen printing techniques respectively. Morphological and electrical properties of the grid have been investigated and compared with a reference evaporated one. High quality and conformal zinc grids have been deposited showing very high growth rates up to 3.3 µm min −1 . Zinc grid is successfully deposited as front electrode for CIGS solar cells that are fabricated by a variety of deposition processes. Efficiency (16.3%) is achieved without antireflection coating on a 0.5 cm 2 co‐evaporated absorber and 14.8% on an electrodeposited one. Using electrodeposition for the growth of the doped ZnO film as well, a 14.1% efficiency is demonstrated on an all‐wet solar cell only composed of layers deposited by atmospheric methods—from absorber to metallic grid. The process is then applied to a 4.2 cm 2 cell as a first step toward large‐scale application. Finally, a zinc grid is deposited on a 0.5 cm 2 silicon heterojunction showing a promising 17% efficiency. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : An atmospheric, fast and low‐cost process of metallization based on electrodeposition of zinc for solar cell front contact is demonstrated. The performances of electrodeposited zinc on CIGS cells are comparable with those of a reference‐evaporated nickel–aluminum grid, yielding efficiencies up to 16.3% on co‐evaporated solar cell and 14.1% on an all‐atmospheric solar cell. Potential application to silicon heterojunction solar cells is also presented.